Immunotherapy Plus Cryotherapy: Potential Augmented Abscopal Effect for Advanced Cancers - Abdo, Joe; Cornell, David L.; Mittal, Sumeet K.; Agrawal, Devendra K. (Frontiers in Oncology, 2018)
Since the 1920s the gold standard for treating cancer has been surgery, which is typically preceded or followed with chemotherapy and radiation, a process that perhaps contributes to the destruction of a patient’s immune defense system. Cryosurgery ablation of a solid tumor is mechanistically similar to a vaccination where hundreds of unique antigens from a heterogeneous population of tumor cells derived from the invading cancer are released. However, releasing tumor-derived self-antigens into circulation may not be sufficient enough to overcome the checkpoint escape mechanisms some cancers have evolved to avoid immune responses. The potentiated immune response caused by blocking tumor checkpoints designed to prevent programmed cell death may be the optimal treatment method for the immune system to recognize these new circulating cryoablated self-antigens. Pre-clinical and clinical evidence exists for the complementary roles for CTLA-4 and PD-1 antagonists in regulating adaptive immunity, demonstrating that combination immunotherapy followed by cryosurgery provides a more targeted immune response to distant lesions, a phenomenon known as the abscopal effect. We propose that when the host’s immune system has been “primed” with combined anti-CTLA-4 and anti-PD-1 adjuvants prior to cryosurgery, the preserved cryoablated tumor antigens will be presented and processed by the host’s immune system resulting in a robust cytotoxic CD8+ T-cell response. Based on recent investigations and well-described biochemical mechanisms presented herein, a polyvalent autoinoculation of many tumor-specific antigens, derived from a heterogeneous population of tumor cancer cells, would present to an unhindered yet pre-sensitized immune system yielding a superior advantage in locating, recognizing and destroying tumor cells throughout the body.